Pengaruh Return on Equity dan Non Performing Finance terhadap Capital Buffer pada Bank Umum Syariah di Indonesia - Ridwan, Muhammad; Yusuf, Nuraini; Indra, Jasmi (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
The background of this research lies in the importance of understanding how financial performance and financing quality influence the capital reserves that banks are required to maintain, especially within the framework of Islamic banking, which follows different principles compared to conventional banks. This study was conducted to examine and analyze the effect of Return on Equity (ROE) and Non-Performing Financing (NPF) on the Capital Buffer of Islamic Commercial Banks (Bank Umum Syariah) in Indonesia during the period of 2016–2022. The research employed a quantitative approach using secondary data obtained from the annual financial reports of five Islamic Commercial Banks in Indonesia from 2016 to 2022. The data analysis techniques used included descriptive statistics, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results showed that Return on Equity (ROE) did not have a significant effect on the Capital Buffer, indicating that bank profitability does not directly influence the level of capital reserves. On the other hand, Non-Performing Financing (NPF) had a significant effect, suggesting that the quality of financing or the level of problematic financing plays a crucial role in determining the capital buffer requirements. Simultaneously, ROE and NPF were found to have a significant effect on the Capital Buffer, implying that although ROE individually does not show a significant impact, in combination with NPF, it contributes to shaping capital policy in Islamic Commercial Banks.